Lipid-lowering and anti-lipase properties of powder fractions of Dichrostachys glomerata fruits - Josiane, Ngatchic Metsagang Therese; Nikaise, Douanla Nodem Forestine; Baudelaire, Ndjantou Elie; Nicolas, Njintang Yanou (Asian Journal of Medical Sciences, 2020)
Background: Fruits of Dichrostachys glomerata have in the last ten years benefited from special attention as a lipid-lowering plant. Recent studies show that biological activities of some plants depend on granulometry of their powder particles. Aims and Objective: The purpose of this study was to assess antihyperlipidemic, hypolipidemic, and anti-lipase properties of powder fractions of the fruits of Dichrostachys glomerata. Materials and Methods: The groups of rats on which the antihyperlipidemic test was done were fed with High Fat Diet and supplemented with powder fractions: ≥180μm, 212–180μm, 315–212μm, ≥315 μm and unsieved powder of Dichrostachys glomerata fruits at dose of 250 mg/kg for four weeks. For the hypolipidemic test, the diet was changed to normal diet and the powder fraction: 212 – 180μm, was given to rats for four weeks. Lipase inhibitory activity was determined using olive oil as substrate. Results: The antihyperlipidemic test showed that powder fractions reduced levels of total cholesterol, LDL-Cholesterol and triglycerides, groups taken powder fractions 212 –180µm and <180µm, presented the lowest values. HDL-Cholesterol levels increased, significant increases were observed in groups fed with powder fractions 315–212µm, 212–180µm, <180µm and unsieved powder. Concerning hypolipidemic test, powder fraction 212–180 µm decreased levels of total cholesterol, LDL-Cholesterol and triglycerides. 86.43% of the activity of pancreatic lipase was reduced to a concentration of 25mg/ml with an IC50 of 5mg/ml. Conclusion: Antihyperlipidemic properties of Dichrostachys glomerata fruits depended on powder fractions. Fraction 180-212μm exhibits hypolipidemic effects. The inhibition of pancreatic lipase is one of the mechanisms which could explain lipid- lowering properties of Dichrostachys glomerata fruits.